Mozambique’s insurgency: a new Boko Haram or youth demanding an end to marginalisation? - Hanlon, Joseph (Africa at LSE, 2018)
Joseph Hanlon argues that Mozambique’s new “Islamic” insurgency is about marginalised youth demanding to be heard, and therefore is similar to anti-establishment protest across the world.
Keywords: *snowball; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Cabo Delgado; L - english / inglês; conflict - violent extremism / conflito - extremismo violento; conflict / conflito; social inclusion & exclusion / inclusão e exclusão social; youth / juventude